2011
DOI: 10.1007/s11806-011-0424-0
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of estimating heavy metal contaminations in floodplain soils using laboratory-based hyperspectral data—A case study along Le’an River, China

Abstract: It is necessary to estimate heavy metal concentrations within soils for understanding heavy metal contaminations and for keeping the sustainable developments of ecosystems. This study, with the floodplain along Le'an River and its two branches in Jiangxi Province of China as a case study, aimed to explore the feasibility of estimating concentrations of heavy metal lead (Pb), copper (Cu) and zinc (Zn) within soils using laboratory-based hyperspectral data. Thirty soil samples were collected, and their hyperspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 19 publications
0
33
1
1
Order By: Relevance
“…Contrary to the present results of regression analysis, several research studies (Al Maliki et al 2014;Liu et al 2011b;Malley and Williams 1997;Pandit et al 2010;Ren et al 2009;Wang et al 2014;Wu et al 2011;Wu et al 2005a;Wu et al 2005b;Xia et al 2007) achieved satisfactory results for PLS prediction of soil metals. In present study, we only measured soil OC/OM and three metals without due respect to other soil active components (clays, Fe/Aloxides, carbonates, etc.…”
Section: Prediction Of Soil Metalscontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to the present results of regression analysis, several research studies (Al Maliki et al 2014;Liu et al 2011b;Malley and Williams 1997;Pandit et al 2010;Ren et al 2009;Wang et al 2014;Wu et al 2011;Wu et al 2005a;Wu et al 2005b;Xia et al 2007) achieved satisfactory results for PLS prediction of soil metals. In present study, we only measured soil OC/OM and three metals without due respect to other soil active components (clays, Fe/Aloxides, carbonates, etc.…”
Section: Prediction Of Soil Metalscontrasting
confidence: 99%
“…Vohland et al (2009) showed that a spectroscopic assessment of trace metals in German floodplain soil by means of active SOC as major predictor is feasible, however, the PLSR accuracies for Zn, Pb, Cu prediction were low (R 2 = 0.56-0.71). Similarly, the spectral region of 400-530 nm, absorption at 630 nm, and absorption ratio of 624/564 nm were found to be dominant spectral proxies of OM/SOC, respectively for prediction of total Cd in river sediments (Xia et al 2007), for Cd in agricultural soils in the Changjiang river delta (Ji et al 2010), and Pb, Cu, Zn in soils (Liu et al 2011b). Recently, Zheng et al (2011) found that prediction of As in soil having lower OM content was better (R 2 = 0.69) than that in soils with of higher OM.…”
Section: Predictions Based On Organic Matter or Organic Carbonmentioning
confidence: 93%
“…Many of these studies tended to identify comparatively obvious spectral features by metals stress, which often manifests as a higher simulation accuracy of heavy metal content than the field studies. However, the vegetation spectral properties are a function that depends on the many geographical variations and applying the results of the laboratory to the natural environment still needs to be explored [17][18][19]. Field studies that examine the plant response to metal-contaminated soil have mostly focused on old waste deposit sites [1][2][3], river floodplains [19,20], polluted farms [21,22], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metal concentration (HMC) in soil is an important indicator of soil quality, which is hazardous to living species and crop growth (Liu et al, 2011). Traditional approach to obtain HMC relying on field sampling and lab testing is expensive and time consuming (Slonecker et al, 2010).…”
Section: Introductionmentioning
confidence: 99%